Implementasi Aplikasi Sistem Keuangan Desa (Siskeudes) Dalam Meningkatkan Transparansi Pengelolaan Keuangan Di Kecamatan Sintang - Siregar, Muhammad Nabil; Marta, Fitri Yul Dewi; Nalien, Elvira Mulya; Ardieansyah (Universitas Pahlawan Tuanku Tambusai, 2025)
Implementation of the Village Financial System Application (SISKEUDES) in Increasing Transparency of Financial Management in Sintang District. This study aims to analyze the implementation of the Village Financial System application (SISKEUDES) in increasing transparency of village financial management in Sintang District. SISKEUDES is expected to encourage accountability and openness of village financial information to the community. This study uses a qualitative approach with a case study method. Data were collected through in-depth interviews with village officials, village treasurers, and the community, as well as analysis of village financial report documents before and after the implementation of SISKEUDES. The results of the study indicate that the implementation of SISKEUDES has increased transparency of village financial management through structured reporting features, real-time recording, and easier access for the community to monitor the allocation and use of village funds. However, obstacles such as limited human resources and internet infrastructure are still challenges in optimizing the system. SISKEUDES has proven effective in increasing transparency of village finances in Sintang District, although it is necessary to increase human resource capacity and infrastructure support to maximize its benefits. The implications of this study can be a reference for local governments in strengthening accountable village financial governance.